Polymer-mixed Sb2Te3/Te nanocomposites exhibiting p-type to n-type conduction reversal and thermal conductivity reduction - Dilip Kumar Meena; Rapaka S C Bose; A M Umarji; D Arvindha Babu (Materials Research Express, 2023)
Sb _2 Te _3 -based materials are potential room-temperature thermoelectric materials. In the present work, we choose polycrystalline Sb _2 Te _3 /Te nanocomposites and utilize Poly Methyl Methacrylate (PMMA) to reduce the thermal conductivity of Sb _2 Te _3 samples. PMMA and polycrystalline Sb _2 Te _3 /Te were well mixed using ball milling. Pellets have been made by the cold press method. Thermoelectric transport properties of Sb _2 Te _3 /Te nanocomposites: composition, microstructure, and analysis are found to be influenced by PMMA. With increasing PMMA concentration a p-type to n-type transition has been observed because there are fewer charge carriers or the composites have a higher resistance. It is also observed that the thermal conductivity of Sb _2 Te _3 /Te nanocomposites decreases as the PMMA increases. This research paves the way for making the best thermoelectric materials by reducing thermal conductivity through the use of polymers.